A Novel MXene/Ecoflex Nanocomposite‐Coated Fabric as a Highly Negative and Stable Friction Layer for High‐Output Triboelectric Nanogenerators. Issue 1 (23rd November 2020) - Salauddin, Md; Rana, S M Sohel; Sharifuzzaman, Md.; Rahman, Muhammad Toyabur; Park, Chani; Cho, Hyunok; Maharjan, Pukar; Bhatta, Trilochan; Park, Jae Yeong
Abstract: The triboelectric material properties and mechanical stability of the contact layer are vital to achieving durable triboelectric nanogenerators (TENGs) with high output performance. Herein, a novel MXene/Ecoflex nanocomposite is introduced as a promising triboelectric material because of its highly negative triboelectric properties and mechanical stability. The MXene/Ecoflex nanocomposite with a fabric‐based waterproof TENG (FW‐TENG) is fabricated and designed to universally harvest energy from various human motions as well as the natural environment (rain and wind). The fabricated FW‐TENG delivers a maximum output peak power of 3.69 mW and a power density of 9.24 W m −2, respectively, at a matching load resistance of 4.5 MΩ under a frequency of 4.5 Hz and a force of 8 N. Furthermore, the applicability of this device in various products is investigated. The FW‐TENG can protect against a crash caused by rainy and humid weather. An FW‐TENG‐based self‐powered smart active device that detects motion on a carpet is demonstrated and is equipped with sleep monitoring motion sensors. The FW‐TENG not only has self‐powered benefits and excellent mechanical amenability but is also exceptionally reliable and stable against water intrusion, which are important characteristics to realize next‐generation wearable/portable technologies. Abstract : A highly flexible and high‐performance triboelectric nanogenerator (TENG) based on a novel MXene/Ecoflex nanocomposite with nylon‐ and silver‐coated conductive fabric for the contact–separation mode waterproof TENG (FW‐TENG) is fabricated and designed to harvest energy from various sources including human motions (e.g., wrist, elbow, knee, and foot) and the natural environment (rain and wind).